IMPLEMENTASI WEB SCRAPING DAN ETL UNTUK PEMBUATAN PETA INTERAKTIF SEBARAN DESTINASI WISATA GEOPARK CILETUH MENGGUNAKAN PYTHON - Dinata, Fajar Sukarsa; Saepudin, Sudin; Irawan, Carti (STKIP PGRI Tulungagung, 2026)
Ciletuh-Palabuhanratu Geopark has rich geological and cultural diversi-ty, but information related to its tourist destinations is still limited. The information available on the official website is scattered on various pages, so users have to open many pages to get complete data about each destination. This research aims to build an interactive map that integrates all tourist destination information in one platform. The web scraping method is used to collect data from the official Ciletuh Ge-opark website. The data obtained is then visualized in an interactive map using Folium, with features of colored markers, marker clusters, and informative popups. The results showed that web scraping can be used effectively to collect and present tourist information in an inte-grated manner. The resulting interactive map allows users to access des-tination information in a single view, making data search easier for tourists and stakeholders. This research contributes to the development of digital-based tourism information systems, improves data accessibil-ity, and supports sustainable ecotourism planning in Ciletuh Geopark.